A concise handbook of the Indian economy in the 21st century - Goyal, Ashima (New Delhi : Oxford University Press, 2015)
Contributed articles.
Includes bibliographical references and index.
Keywords: Economic development -- India -- History -- 21st century; India -- Economic conditions -- 21st century; India -- Economic policy -- 1991-